2018 IEEE 5th International Conference on Engineering Technologies and Applied Sciences (ICETAS) 2018
DOI: 10.1109/icetas.2018.8629206
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Replacement of Natural Sand by Manufactured Sand on the Properties of the Concrete

Abstract: The natural sand which excavated from river bed is used to produced conventional concrete. Depletion of natural sand cause the environmental problem and hence sand excavating is restricted by government which resulted in shortage and drastically increase in its cost. In order to fulfil the necessity of fine aggregates, an alternative material like M sand can be used in concrete. M sand is obtained by crushing the rocks. In this paper, conventional mix 1:2.32:2.82 (M20) with water to binder ratio is maintained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…This paper is an extension of work originally presented in conference IEEE 5th International Conference on Engineering Technologies & Applied Sciences, 22-23 Nov 2018, Bangkok Thailand [1]. In the world, fine aggregate, probably natural sand, composes up to 30% of the volume of concrete, it is around 4 billion tons sand is required to meet annual necessity of concrete production [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper is an extension of work originally presented in conference IEEE 5th International Conference on Engineering Technologies & Applied Sciences, 22-23 Nov 2018, Bangkok Thailand [1]. In the world, fine aggregate, probably natural sand, composes up to 30% of the volume of concrete, it is around 4 billion tons sand is required to meet annual necessity of concrete production [2].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the limiting resources of river sand, alternatively M sand can be used. [1]- [10]. The Manufactured sand is produced by crushing the rocks [5] [10].…”
Section: Introductionmentioning
confidence: 99%
“…The American standard ASTM C 33 [116] accepts only up to a limit of 7% of fine material passing through the 150 µm sieve, and NBR 7211/2022 [117] accepts between 10% and 12%, maximum, (for concrete subjected to surface wear and for concrete protected from surface wear, respectively). Some authors [86,89,97,100,118] showed that the average percentage of retention on the sieve following 150 µm/75 µm varied from 5.5% to 8.5%.…”
Section: Resultsmentioning
confidence: 99%
“…3.2.1. Workability Despite the variation in the effect of stone dust on concrete workability due to the different physical characteristics of SD found in the various mining companies around the globe, such as angularity, fineness modulus, morphology, specific surface area, and specific mass, most of the research results [8,87,90,[94][95][96]100,[102][103][104][107][108][109][110]121] conclude that the higher the level of substitution of stone dust, the higher the content of fines and thus the greater specific surface area, leading to lower workability of concrete in the fresh state. Also, according to data from these publications, the workability of fresh concrete made with stone dust replacing natural sand as fine aggregate suffers a reduction in comparison with reference concrete (with 0% replacement).…”
Section: How Does Stone Dustmentioning
confidence: 99%
“…The scarcity or insufficient supply of excellent quality sand has resulted in a significant price increase, which has an impact on building costs [1]. This motivated academics and experts in the construction industry to search for a suitable material that is acceptable to the environment and can be effectively used in construction practices as an alternative material while reducing production costs [2]. However, one possible alternative material is manufactured sand.…”
Section: Introductionmentioning
confidence: 99%